ENSURING THE IMPLEMENTATION OF COMMERCIALIZATION STRATEGIES FOR SATELLITE SERVICES IN THE DIGITAL ECONOMY - Viacheslav V. Makedon; Liudmyla I. Yarmolenko; Tetiana V. Chumak; Olena Ye. Zaporozhchenko (Academy Review)
The article explores the mechanisms and strategies that can be applied at the initial stages of developing a satellite service for its successful market entry and consolidation. The importance of strategic planning is emphasized through the analysis of the technical and economic aspects of the service, which must meet the expectations of potential consumers and demonstrate its competitive potential. The authors consider various commercialization strategies adapted to the needs of digital satellite service developers, taking into account the market’s transition to a service model and online activities. The article also examines approaches to the development and promotion of satellite services, focusing on the need to analyze global market demands, competitor strategies, and the potential of innovative solutions to address specific economic challenges. Developing a technological strategy and implementing it through the management system for bringing satellite services to market is key to achieving high competitiveness and effective pricing at all stages of the service life cycle. The article provides a detailed overview of the management system methodology used to determine these quantitative indicators, with a particular emphasis on integrating strategic planning with operational management. The authors argue that a successful commercialization strategy must be flexible and capable of quickly adapting to changes in market conditions, consumer demands, and technological innovations. Such flexibility contributes to effectively satisfying consumer needs and increasing service efficiency. Particular attention is given to the use of quantitative assessments and analyses to determine sales potential, identify key risks, and consider opportunities for innovative development and the expansion of the market niche for satellite services. The authors emphasize the importance of integrating strategic planning with analytical tools to optimize decision-making, allowing not only the prediction of future trends but also a flexible and timely response to them. The article offers a holistic view of the development and commercialization process of satellite services, highlighting the need for a comprehensive analysis of market conditions, the competitive environment, and the potential for innovation.